Sudden Commencements and Impulses in Kodaikanal magnetograms -their hourly frequency - SRINIVASAMURTHY, B. (MAUSAM, 1959)
The diurnal variation in the frequencies of sudden commencements (SCs) and sudden impulses (SIs) at Kodaikanal (10.2°N, 77.5°E) is analysed from the data for the period 1949-1957.The hourly frequency curve of SCs and SIs (combined) has little resemblance to the curve obtained by Newton from his analysis of Greenwich-Abinger record. The results of harmonic analysis show a nearly semi-diurnal trend the distribution of storm sudden commencements (SSCs); this, however, is small. The hourly frequencies of SIS show s significant diurnal variation with an afternoon maximum and a forenoon maximum and a secondary minimum around 18h local time and a secondary maximum around 08h. These results are also compared with those obtained by Ferraro Parkinson and Unthank.